Oral health-related quality of life and prosthetic status of nursing home residents with or without dementia - Klotz, Anna-Luisa; Hassel, Alexander J.; Schröder, Johannes; Rammelsberg, Peter; Zenthöfer, Andreas (Clinical interventions in aging, 2017)
PURPOSE: The objective of this cross-sectional study was to evaluate the effect of prosthetic status on the oral health-related quality of life (OHRQoL) of nursing home residents with or without dementia. METHODS: The study was performed in 14 nursing homes across the federal state of Baden-Württemberg, Germany. All eligible participants were included, and general and medical information and information about their dental and prosthetic statuses were collected. The Geriatric Oral Health Assessment Index (GOHAI) was administered to evaluate OHRQoL. The Mini-Mental State Examination (MMSE) served to classify participants into living or not living with dementia according to the established cutoff value for dementia (MMSE <24). Parametric bivariate statistics and logistic regression models were used to analyze data at P<0.05. RESULTS: A total of 169 participants were included in this study. The mean age of the participants was 82.9 years. A total of some 70% of the sample was living with dementia. The mean GOHAI score along the sample was 49.1 (8.3), and 41% of the sample reported substantially compromised OHRQoL (GOHAI <50). OHRQoL was statistically similar for people with or without dementia (P=0.234); objective oral health was also similar in both groups (P>0.05). The number of teeth (odds ratio [OR]: 2.0), the type of prosthetic status (OR: 6.5), and denture-related treatment needs (OR: 2.4) were the major factors significantly affecting OHRQoL (P<0.05). CONCLUSION: The OHRQoL of elderly nursing home residents is substantially compromised. Several prosthetic treatment needs for residents living with or without dementia were identified. Edentulism without tooth replacement and having <5 teeth resulted in an increased risk of substantially compromised OHRQoL. Further studies should be conducted to determine whether improvements in prosthetic status can increase OHRQoL.